PEMBUATAN GAME THE LEGEND OF BENGKULU MENGGUNAKAN RPG MAKER VX ACE - Arif Rangga Wijaya; Indra Kanedi; Ricky Zulfiandry (Jurnal Media Infotama, 2023)
ABSTRACT :Games are a means of entertainment for all ages. The game is unmistakably has a very rapid development, ranging from games genre action, RPG, FPS, to arcade games. RPG or the term of Role Playing Game where players play a role, generally the player plays the main character (Protagonist). The development of the Protagonist depends on how the player takes steps in the game. In this research, the writer develops a fictional game using the RPG Maker VX ACE engine. The writer collects data through observations of the movement of RPG games in the game world. There is a game-making stage that was carried out earlier, namely concept design and game storyline creation, as well as game design to the trial stage where testing was made based on the purpose of making the game. The RPG game of The Legend of Bengkulu has been successfully designed where players can develop their own characters. This game is also expected to improve the player's ability to solve the puzzles given in the game. With this game, the writer also hopes that players can get to know the famous history in the Bengkulu area, which is none other than Fort Marlborough.